(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2026)
The current challenges and problems in the agriculture of the Republic of Armenia create significant difficulties in developing measures aimed at increasing the efficiency of land and water resource use. The increasing scale of unused lands, fragmentation of small land plots, as well as the lack of information on the spatial organization of land plots slow down the development of agriculture, hinder the activation of production and attraction of investments. Efficient use of agricultural lands is important for agriculture, and digital technologies currently create ample opportunities for their study. Especially in the context of fragmented, unused land plots and climate change, the measures developed often require comprehensive scientific justification. Ultimately, this will allow proposing such measures to increase the efficiency of their use as land amalgamation, consolidation, creation of large land users, as well as ensuring conditions for sustainable, developing and viable agriculture. The Normalized Difference Vegetation Index (NDVI) and the Normalized Difference Humidity Index (NDMI) are currently widely used to assess the efficiency indicators of agricultural land use. Their numerical values are obtained as a result of appropriate analysis and evaluation of satellite images. The NDVI index is an important tool for long-term assessment of vegetation cover changes, while NDMI changes indicate changes in the moisture level of vegetation.